PROPOSTA DE PLANO DE INSPEÇÃO PROATIVO PARA DISPOSITIVOS ELETRÔNICOS INTELIGENTES NA SEGURANÇA OPERATIVA DE SISTEMAS DE ENERGIA ELÉTRICA. - GERUDE, Bruno Gomes (2017)
As society's dependence on energy increases, the regulatory agencies' demands grow with the electric power concessionaires for quality and continuity. On the other hand, in particular, the Brazilian electrical system is much more complex due to the increase in other transmission lines, substations, direct current systems and the use of generation plants from different sources, which imposes on energy companies the adoption Strategies and procedures that guarantee greater reliability to these assets. The use of Intelligent Electronic Devices (IEDs) allows the operation of electric power systems to make faster and more assertive decisions, however, the maintenance and inspection strategies in these equipments are not even among the companies in the sector, and this has led to some professionals to abandon the idea of proactive inspection. In this work a broad approach is taken on the subject, from the perspective of manufacturers' manuals, Reliability Centered Maintenance theory (RCM) and under international norms and guidelines. It is presented a research with eight companies of the Brazilian electrical sector and a survey of information in two substations of the National Interconnected System, with evaluation of the performance of the installed IEDs which includes the construction of failure curves, stratification of defects by subsystems and comparison between the families of IEDs in these facilities. At the end, a plan of periodic inspection is proposed in these devices using a methodology based on multicriteria analysis to define periodicities.